Making decisions about supplement use - Maughan, R. J.; Shirreffs, S. M.; Vernec, A. (International Journal of Sport Nutrition and Exercise Metabolism, 2018)
The use of dietary supplements is widespread among athletes in all sports and at all levels of competition, as it is in the general population. For the athlete training at the limits of what is sustainable, or for those seeking a shortcut to achieving their aims, supplements offer the prospect of bridging the gap between success and failure. Surveys show, however, that this is often not an informed choice and that the knowledge level among consumers is often low and that they are often influenced in their decisions by individuals with an equally inadequate understanding of the issues at stake. Supplement use may do more harm than good, unless it is based on a sound analysis of the evidence. Where a deficiency of an essential nutrient has been established by appropriate investigations, supplementation can provide a rapid and effective correction of the problem. Supplements can also provide a convenient and time-efficient solution to achieving the necessary intake of key nutrients such as protein and carbohydrate. Athletes contemplating the use of supplements should consider the potential for both positive and negative outcomes. Some ergogenic supplements may be of benefit to some athletes in some specific contexts, but many are less effective than is claimed. Some may be harmful to health of performance and some may contain agents prohibited by anti-doping regulations. Athletes should make informed choices that maximize the benefits while minimizing the risks.